Risk factors and mortality associated with permanent pacemaker after surgical or transcatheter aortic valve replacement: Early versus late implantation. Issue 12 (21st September 2022) - Bin Mahmood, Syed Usman; Mori, Makoto; Amabile, Andrea; Prescher, Lindsey; Forrest, John; Kaple, Ryan; Geirsson, Arnar; Mangi, Abeel A.
Abstract: Introduction: Inflation of transcatheter aortic valve replacement (TAVR) procedures compared to surgical aortic valve replacement (SAVR) has increased the number of patients requiring a postprocedure permanent pacemaker (PPM). We investigate the impact of PPM on mid‐term mortality comparing SAVR versus TAVR procedures and risk factors for early and late (>14 days) need of PPM. Methods: We conducted a retrospective, single‐center evaluation of 903 patients that underwent either SAVR or TAVR procedures at the Yale New Haven Hospital from 2012 to 2017. Patients were stratified into PPM and non‐PPM groups. We performed Kaplan–Meier and Cox proportional hazard analysis to characterize mid‐term mortality. Further subgroup analysis was performed to identify risk factors for early and late PPM implantation in the TAVR cohort. Results: There was no correlation between PPM implantation and mid‐term mortality in both SAVR (hazard ratio [HR] = 0.69; confidence interval [CI] = 0.21–2.30; p = .56) and TAVR (HR = 0.70; CI = 0.42–1.17; p = .18) patients. The presence of the right bundle branch block (Odds ratio = 24.07; 95% CI = 2.34–247.64, p = .007) was associated with higher odds of early PPM requirement after TAVR procedures. Conclusion: PPM placement after SAVR or TAVR procedures is not associated with increased mid‐term mortality. In‐depth characterization of risk factors for early and late PPM implantation will require further analysis in the growing TAVR patient population.